Treatment of third molars: modern approaches and creative solutions (Herald of the National Children's Medical Center, 2024)
Third molars (wisdom teeth) are one of the most widely discussed issues in medicine due to their positioning and anatomical structure, which complicates treatment. This article examines the effectiveness of modern diagnostic and treatment methods, as well as new surgical techniques. Background. The aim of this article is to analyze the complications following third molar (wisdom tooth) extraction and to study the methods for their prevention and treatment.Materials and methods. The study was conducted based on a retrospective analysis. Between 2021 and 2024, complications following third molar extraction were recorded in 108 patients. During the study, factors such as patients’ gender, age, tooth position, and extraction method were taken into account.Results. Successful outcomes were observed in 85% of patients treated with surgical methods. The majority of patients achieved full recovery within a week after surgery, and complications were rare.Conclusion. The results of the study indicate that surgical removal of the tooth is the most effective method for patients. The use of modern diagnostic technologies and laser techniques significantly reduces surgical complications and accelerates the recovery process for patients.
Keywords: third molar; wisdom tooth; surgical procedure; treatment methods; diagnostics; tooth extraction complications; innovative technologies